1982
DOI: 10.1128/mcb.2.8.904
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the capacity for O6-methylguanine removal from DNA in human lymphoblastoid cells studied by cell hybridization.

Abstract: Hybrids were made between a ouabain-resistant, thioguanine-resistant human lymphoma line able to remove O6-methylguanine from its DNA (Mex+) and human lymphoblastoid lines deficient in this capability (Mex-). The formation of hybrids was confirmed by chromosomal analysis. Hybrid cells had an O6-methylguanine removal capacity per mole of guanine about one third to one half that of the Mex+ parents, i.e., about the same per cell. Cell hybrids removed the same amount of the alkylation adduct 3-methyladenine as di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1985
1985
1990
1990

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…First, the intracellular distributions of tRNA MeTase and the repair enzymes are similar-the major fraction of both enzymes is found in the cytoplasm, although both are present in the nucleus (19,32). Second, Ayres et al (33) found no evidence for a diffusible regulator able to activate or repress the MeTase gene in hybrids between Mex+ and Mex-cells. This is compatible with the full expression of both sets of 06MeGua MeTase genes and the subsequent inactivation of a fraction of the enzyme molecules.…”
Section: Discussionmentioning
confidence: 99%
“…First, the intracellular distributions of tRNA MeTase and the repair enzymes are similar-the major fraction of both enzymes is found in the cytoplasm, although both are present in the nucleus (19,32). Second, Ayres et al (33) found no evidence for a diffusible regulator able to activate or repress the MeTase gene in hybrids between Mex+ and Mex-cells. This is compatible with the full expression of both sets of 06MeGua MeTase genes and the subsequent inactivation of a fraction of the enzyme molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Karyotypically, they consist of two populations, a majority (-90Y0) that has 46 chromosomes and a minority with 48 chromosomes. L33 cells were derived from a female with infectious mononucleosis and have been described by Ayres et al [24]. Currently they maintain the original number of 47 chromosomes.…”
Section: Cells and Plasmidsmentioning
confidence: 99%
“…Some subclones of human HeLa S cells-e.g., one obtained from the Massachusetts Institute of Technology Cell Culture Center (HeLa M)-are Mex-, while another subclone-obtained from the American Type Culture Collection (HeLa S3)-has the highest level of MGMT (1.8 x 105 molecules per cell) among all mammalian lines tested (10,17). MGMT expression, while predictable in human/human somatic cell hybrids, appears to be controlled by multiple genetic and epigenetic factors in Mex+ human-Mex-rodent hybrid cells (17)(18)(19). Transformation of Mer+ human cells with simian virus 40 frequently induces the Mer-phenotype, which is observed most commonly in tumor lines (9,15,18).…”
mentioning
confidence: 99%